Strategies to improve tumor penetration of nanomedicines through nanoparticle design. (16th April 2018) - Zhang, Ya‐Ru; Lin, Run; Li, Hong‐Jun; He, Wei‐ling; Du, Jin‐Zhi; Wang, Jun
Abstract : Nanoparticles (NPs) have emerged as an effective means to deliver therapeutic drugs for cancer treatment, as they can preferentially accumulate at tumor site through the enhanced permeability and retention effect. Various forms of NPs including liposomes, polymeric micelles, and inorganic particles have been used for therapeutic applications. However, the therapeutic benefits of nanomedicines are suboptimal. Although many possible reasons may account for the compromised therapeutic efficacy, the inefficient tumor penetration can be a vital obstacle. Tumor develops characteristic pathological environment, such as abnormal vasculature, elevated interstitial fluid pressure, and dense extracellular matrix, which intrinsically hinder the transport of nanomedicines in the tumor parenchyma. The physicochemical properties of the NPs such as size, shape, and surface charge have profound effect on tumor penetration. In this review, we will highlight the factors that affect the transport of NPs in solid tumor, and then elaborate on designing strategies to improve NPs' penetration and uniform distribution inside the tumor interstitium. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Advanced designing strategies can be exploited to improve tumor penetration and therapeutic efficacy of cancer nanomedicines.